Applications of CRISPR/Cas9 in the Synthesis of Secondary Metabolites in Filamentous Fungi - Jiang, Chunmiao; Lv, Gongbo; Tu, Yayi; Cheng, Xiaojie; Duan, Yitian; Zeng, Bin; He, Bin (Frontiers in Microbiology, 2021)
Filamentous fungi possess the capacity to produce a wide array of secondary metabolites with biological activities and diverse structures, such as lovastatin and swainsonine. With the advent of the post-genomic era, increasing amounts of cryptic or uncharacterized secondary metabolite gene clusters are being discovered. However, owing to lack of a versatile, comparatively simple and highly efficient genetic technique, the broader exploration of industrially important secondary metabolites has been hampered far. With the emergence of the CRISPR/Cas9 technology, this dilemma may be alleviated as this advanced technique has revolutionized genetic research and opened up doors for exploitation and discovery of new bioactive compounds. In this review, we introduce the principle of the CRISPR/Cas9 system in detail and collate the latest applications of CRISPR/Cas9-mediated genome editing in filamentous fungi. We also briefly introduce the specific applications of the CRISPR/Cas9 system and CRISPRa for the improvement of secondary metabolite content and discovery of new biologically active compounds using specific examples. Additionally, modulating the common challenges and deficiencies of using CRISPR/Cas9-based genome editing methods in the secretion of secondary metabolites by filamentous fungi and future perspectives of CRISPR/Cas9 strategy are highlighted and discussed.